PERAN UNITED NATIONS OFFICE ON DRUGS AND CRIME (UNODC) DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA TAHUN 2009-2014 - SYAHTRI KURNIA UTOMO; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research describes role of an Internatinal Organizations, United Nations on Drugs and Crime (UNODC) on fighting the corruption in Indonesia, 2009-2014. The numbers of Indonesia’s corruption quantity is increasing and sreading from lowest level to the highest level. Corruption in Indonesia always growths through year to year, not only the numbers of corruption rates, but also the numbers of Indonesia’s financial loss. Fighting corruption effort quality has to be modified and advanced by Indonesia law enforcment agencies on creating just and prosper Indonesia.This research theoretically has built with pluralism perspectives on International Relations and supported by International Organizations Roles theories, and also the concept of Organized Crime. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Scope of this research is the role of UNODC on the corruptions fighting efforts of Indonesia.This research also proves that UNODC roles on handling corruption is sufficient. UNODC preventive action that has been offered to Indonesia law enforcement agencies, excluded, seminars, trainings, discussions, and workshop cooperated with national and international institutions. Considering the survey result by International Transparency, Indonesia’s score always increasing from year to year. This is also considered by UNODC roles and contributions on fighting corruptions task in Indonesia.Keywords: Corruption, UNODC Roles and Preventife Action.